Analysis of Information Technology Governance Using COBIT 2019 Framework (Case study: PT. Bangkit Anugerah Bersama) - Steven Chrisdianta Putra; Agustinus Fritz Wijaya (Journal of Information System and Informatics, 2022)
PT. Bangkit Anugerah Bersama is a pharmaceutical company that focuses on distributing medical devices to various pharmacies in major cities in Indonesia, in carrying out its business processes PT Bangkit Anugerah Bersama has implemented information technology and continues to grow to create innovations. innovation in utilizing technology, in this case, it is necessary to design IT governance at PT Bangkit Anugerah Bersama, so this research was made which aims to design IT governance using COBIT 2019 so that business processes and IT implementation can run in harmony. The method used in this research is descriptive by conducting interviews with IT staff at PT Bangkit Anugerah Bersama. The analysis of the design of information technology governance in this study uses a design toolkit that includes 10 design factors from COBIT 2019. Based on the research conducted, it produces a design of information technology governance with a total of 4 domains that are important for the company, this is taken from sub-sections that have value ≥ 50 of them are BAI06, BAI03, BAI11 and BAI02.